2014
DOI: 10.1371/journal.pone.0115051
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse Imaging for Non-Invasive Assessment of Renal Histopathology in Chronic Kidney Disease

Abstract: ObjectiveTo investigate the stiffness values obtained by acoustic radiation force impulse (ARFI) quantification in assessing renal histological fibrosis of chronic kidney disease (CKD).Methods163 patients with CKD and 32 healthy volunteers were enrolled between June 2013 and April 2014. ARFI quantification, given as shear wave velocity (SWV), was performed to measure renal parenchyma stiffness. Diagnostic performance of ARFI imaging and conventional ultrasound (US) were compared with histologic scores at renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 30 publications
7
80
3
2
Order By: Relevance
“…With regard to mean SWS values in healthy adult kidneys our results in pediatric patients show lower mean values: Hu et al reported a SWS of 2.81 m/s with a 4C1 ultrasound probe [14], whereas Bota et al found SWS values in adult kidneys with a mean of 2.49 m/s for the right and 2.36 m/s for the left kidney using a 9L4 ultrasound probe [28].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…With regard to mean SWS values in healthy adult kidneys our results in pediatric patients show lower mean values: Hu et al reported a SWS of 2.81 m/s with a 4C1 ultrasound probe [14], whereas Bota et al found SWS values in adult kidneys with a mean of 2.49 m/s for the right and 2.36 m/s for the left kidney using a 9L4 ultrasound probe [28].…”
Section: Discussioncontrasting
confidence: 56%
“…A study in adult kidneys with and without pathology revealed an inter-observer agreement assessed by ICC of 0.68 for healthy and 0.75 for pathologic kidneys [33]. Likewise, Hu et al reported a good inter-observer agreement for adult kidneys with chronic kidney disease of 0.63 [14]. A considerably lower inter-observer agreement was reported by Syversveen et al Their inter-observer variability between kidney tissues of renal allografts of adults revealed an ICC of 0.31 [35].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the native kidney, human studies have reported various markers associated with increased kidney stiffness: estimated glomerular filtrate rate (eGFR) [23,28,29], urinary albumin / creatinine or protein / creatinine ratio [30,33], serum creatinine [23,29], urea nitrogen [23], elasticity values in healthy native kidneys [23][24][25][26][27][28][29][30][31][32][33]35], kidney biopsies [25], other imaging tests etc [24,26,35]. Thus, there are studies finding no significant correlation between markers of chronic kidney injury and elasticity of renal parenchyma in native [27] or transplanted kidney [48,51], and also studies which could not prove a significant difference of elasticity between different stages of CKD [23,25]; in addition, it has been reported an increased intra-subject variability of results in CKD versus healthy controls [33] or a higher influence of arteriosclerosis markers, such as pulsatility index or resistivity index, on kidney stiffness than eGFR [28].…”
Section: Evaluating Fibrosis In Native Kidney With Us Elastographymentioning
confidence: 99%
“…Transdüserin tekrarlayan kompresif hareketi sırasında hedef dokudan gelen eko sinyallerinin bozulmalarının analiz edilmesi ile doku elastisitesi ölçülmektedir (8) (17). Bu çalışmada histolojik skor ile elastisite skoru arasındaki güçlü ilişki KBY hastalarında ve diğer renal hastalarda fibrozisi belirlemede elastografinin biyopsinin yerini alabileceği düşüncesini doğurmuştur.…”
Section: Serbest El Tekniğiunclassified